Optimisation of an On-grid Hybrid Energy System: A Case Study of the Main Campus of the University of Abuja, Nigeria - Paul Adah Ondachi (ABUAD Journal of Engineering Research and Development)
The challenge of meeting the energy demands of institutions and organisations in an economically viable and environmentally friendly manner is becoming more and more complex especially in developing countries like Nigeria. This work presents a resilient hybrid renewable energy system to supply the electric power requirement of the main campus of the University of Abuja, Nigeria, estimated as 900 kW at a consumption rate of 6300 kWh/day. HOMER software was used as the modelling tool for simulations, optimizations, and sensitivity analyses carried out to explore the feasibility of utilizing Abuja’s (MSW) in hybrid with the mini hydro power potential of River Wuye and solar PV resources to meet the load demand of the campus. The hybrid plant has the following component specifications:hydro resourcenominal flow rate is 14.5 m3/s; maximum head is 10 m and potential capacity is 885 kW;MSW plant specifications were determined to be 500 kW capacity, waste treatment of 2.3 ton/day; lower calorific value for MSW of 15.84 MJ/kg with the solar PV component having a capacity of 500 kW. Total installation cost for the hybrid plant for the 2 MW hybrid plant was determined to be ₦5.44 billion (US$7.225 million) with annual energy generation calculated to be 799,000 kWh/yr. The net present cost for the simulated system was found to be ₦ 9.37 billion ($12,486,120) with the corresponding LCOE being ₦55.2/kWh ($0.0736/kWh). The carbon emission was estimated to be 7.33 g per day which approximates to a net zero emission, demonstrating the environmental friendliness of renewable energy sources utilised. Sensitivity analysis performed on the system using project life span, inflation rate, solar irradiance, MSW’s lower heating value (LHV), capacity shortage and the annual average volumetric flow rate of River Wuye showed that the net present cost increased with increasing plant life while the levelized cost of energy reduces with increasing life from ₦55.02/kWh for plant life of 25 years to ₦43.73/kWh for 30 years.